Pemberdayaan Ekonomi Kreatif Ibu Rumah Tangga Kelurahan Air Tawar Timur - Astari, Silvy; Putriana , Vima Tista; Suhanda, Mya Yuwanita; Amrullah, Amrullah (Civiliza Publishing, 2024)
As the prices of all necessities increase, people are asked to be creative in meeting their daily needs. Apart from saving money and managing finances well, people can be empowered by providing their own basic needs. Therefore, community service is carried out in the Air Tawar Timur Village, namely making clothes washing soap and dish washing soap by providing samples, providing free samples and materials. It is hoped that this can minimize routine expenses and can be developed into a source of income by making this product independently and marketing it. The results show that the people of Air Tawar Timur Village are very enthusiastic and have the desire to implement the training that has been provide